2000
DOI: 10.4141/s99-106
|View full text |Cite
|
Sign up to set email alerts
|

Sewage water irrigation effects on some potentially toxic trace elements in soil and potato plants in northwestern India

Abstract: . 2000. Sewage water irrigation effects on some potentially toxic trace elements in soil and potato plants in northwestern India. Can. J. Soil Sci. 80: 465-471. Sewage water is used for irrigation to improve crop yields, but it may affect the soil and crop quality. The effects of discharging the effluents of a leather complex on the concentrations of some potentially toxic elements (Cu, Fe, Mn, Zn, Al, As, Cr and Ni) in sewage water and the effects of irrigation with contaminated sewage water on the concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
43
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(52 citation statements)
references
References 6 publications
6
43
3
Order By: Relevance
“…But the soil used in their experiment contained between 640 and 693 mg Zn/kg of dry matter. Brar et al (2000) analysed haulms and tubers of potatoes grown in the field (Cambisols) irrigated with water contaminated by trace elements. Their experimental results showed different dynamics of zinc uptake during vegetation and efforts of plants to protect chosen parts against negative effects of higher Zn concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…But the soil used in their experiment contained between 640 and 693 mg Zn/kg of dry matter. Brar et al (2000) analysed haulms and tubers of potatoes grown in the field (Cambisols) irrigated with water contaminated by trace elements. Their experimental results showed different dynamics of zinc uptake during vegetation and efforts of plants to protect chosen parts against negative effects of higher Zn concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, on a long term basis, the TMWW reuse may contribute to the accumulation of these nutrients, and especially heavy metals in the soil, with all possible adverse effects on plants, humans and animals (Yadav et al 2002;Brar et al 2000;Gupta et al 1998;Som et al 1994;Pescod 1992;Feign et al 1991).…”
mentioning
confidence: 96%
“…Mitra & Gupta (1999) has reported that the contents of heavy metals in sewage irrigated radish, gourd, spinach and cauliflower around Calcutta were comparatively 2 to 40 times higher than the non-sewage irrigated vegetables. Brar et al (2000) also reported higher accumulation of metals in leaves and tubers of potato grown on sewage irrigated soils as compared with ground water irrigated soils. Leafy vegetables and root crops are known to accumulate higher amounts of heavy metals than grain crops.…”
Section: Effect On Plantsmentioning
confidence: 95%
“…The concentrations of heavy metals at all the locations increased with the sewage water irrigation. Gupta et al (1986) and Narwal et al (1993) found that the application of sewage water on agricultural land for long period increased the total content of Zn, Mn, Cu, Pb, Ni and Cd in soils of Haryana ( TW -Tube well-irrigated soil, SW -Sewage-irrigated soil Source (Brar et al, 2000;Narwal et al, 1993Narwal et al, , 2002Singh & Kansal, 1985b) Source (Gupta et al, 1986(Gupta et al, , 1998Narwal et al, 1993) Build up of heavy metals in sewage water irrigated soils at other cities has also been reported. Mitra & Gupta (1997) has reported 143 times more accumulation of Cd in sewage effluent irrigated soils around Calcutta over non-sewage irrigated soils, followed by Zn (47 times), Pb (18.5 times), Cr (5.6 times), Co (3.9 times), Cu (3.6 times), Fe (2.4 times) and Ni (2.3 times).…”
Section: Chemical Propertiesmentioning
confidence: 99%